Hyperandrogenism-insulin resistance-acanthosis nigricans syndrome with PCOS and Hashimoto’s thyroiditis: case report - Kulkarni, Amarnath; Srivastav, Shashank Kumar; Susarla, Saraswathi; Kulkarni, Usha; Kumar, C. Ashok; Chikkala, Sunita; Tabassum, Sheik Majeeda (International Journal of Research in Medical Sciences, 2017)
Female hyperandrogenism is a frequent motive of consultation. It is revealed by hirsutism, acne or seborrhea, and disorders in menstruation cycle combined or not with virilisation signs. Several etiologies are incriminated but the hyperandrogenism-insulin resistance-acanthosis nigricans syndrome is rare. A 21-year female, having had a three-year-old secondary amenorrhea, known case of hypothyroidism since 4 years on medication. The exam revealed a patient, hypertensive with blood pressure at 170/110 mmHg with a Body Mass Index (BMI) at 40.08 (Obese Class-3, as per WHO 2004) and a waist measurement of 106cm, a severe hirsutism assessed to be 27 according to Ferriman and Gallwey scale, acanthosis nigricans behind the neck and elbows. The assessment carried out revealed testosteronemia at 1.07 ng/mL, which is more than twice the upper normal of the laboratory. Imaging studies revealed enlarged right adrenal gland, hepatomegaly with fatty infiltration of grade-1 also bilateral polycystic ovaries. The retained diagnosis is HAIR-AN syndrome with polycystic ovaries, hypertension, type-II diabetes mellitus, hypothyroidism since last 4-years and dyslipidemia and was provided with metformin 500 mg thrice daily, spironolactone 25 mg twice daily, atorvastatin 20 mg once daily, telmisartan 20 mg once daily with continuation of eltroxin 50 Mcg for hypothyroidism. To our knowledge this is the first case report of HAIR-AN syndrome in 21 year old female associated with Hashimoto’s thyroiditis, dyslipidaemia, hypertension and type-2-diabetes and this case also highlights about early diagnosis and management of HAIR-AN Syndrome with PCOS and Hashimoto’s thyroiditis which could help prevent long-term sequalae such as cardiovascular disease and endometrial cancer and with the advent of knowledge and availability of health resources we can prevent long-term adverse effects (threefold) on health of women. This woman should be observed for these ailments in later life.